Impact of Smartphone Usage on the Mental Health of Graduate Students in Kathmandu, Nepal - Lamichhane, Basu Dev; Lama, Padam Bahadur; Pandey, Prerna; Lamichhane, Saujan; Khadka, Samiksha; Rana, Srijana (International Journal of Atharva, 2025)
Smartphones are increasing in use among its user that supports learning process of students. Thus, the main objective of the study is to examine the impact of smartphone usage on the mental health of graduate students in Kathmandu. The study adopted descriptive, relational, and causal research designs to investigate the impact of smartphones on students' mental health for better classroom achievement. The study employed smartphone usage as independent variable and mental health of students as dependent variable. The primary sources of cross-sectional data have been collected distributing the structured questionnaire. The 130 questionnaire was distributed to the target respondents and received only 100 (76.92 percent) useful questionnaires from the respondents. The findings of the study revealed a significant relationship between use of smartphone and mental health of graduate students. Thus, the use of smartphone shows that with the increase in use of smartphone there will be positive influence on mental health of graduate students but found insignificant. The implication of the study depicts useful and significant for parents, manufacturers, educational institutions, regulatory bodies, and its users. The novelty of the study reflects the discovery of the influence of smartphone usage in the Nepalese context representing the graduate students located in Kathmandu.